What matters to patients with multiple sclerosis? Identifying patient-relevant attributes using a ranking exercise with open-ended answers from an online survey in Italy - Maria Pia Amato; Ulrik Kihlbom; Emilio Portaccio; Karin Schölin Bywall; Jennifer Viberg Johansson; Sylvia MARTIN; Claudia Niccolai; Guido Pasquini; Filippo Gerli; Sara Della Bella; Matteo Betti (BMJ Open)
Objectives This study aimed to explore what intervention specificities or attributes newly diagnosed individuals with multiple sclerosis (MS) find important and to explore possible reasons behind their evaluations.Design A stepwise approach began with a systematic literature review to identify significant attributes. Patients with MS then assessed these attributes through an online survey, which included a ranking exercise and open-ended questions. Finally, the results were evaluated by the clinical team to select the most relevant factors for personalised care.Setting and participants From June 2023 to December 2023, all consecutive patients referred to the MS Center of Careggi University Hospital were screened for inclusion. Following recruitment, cognitive and physical assessments were administered at the Don Gnocchi Centre. All participants were interviewed by an experienced neuropsychologist.Procedures Participants were enrolled in the RELIABLE clinical trial, which included a ranking exercise and open-ended question. In the ranking exercise, patients prioritised levels of treatment attributes: treatment effects, methods of intervention, type of monitoring, monitoring, mode and mental support. The open-ended questions addressed the reasons behind the level rankings.Results Participants’ rankings revealed the most important levels of each attribute. The highest-ranked method of intervention was disease-modifying treatment, which received 164 points. For mental support, individual psychotherapy was deemed most important with 149 points. Preservation of cognitive function, a key treatment effect, received 144 points. Clinical check-ups were the top type of monitoring with 129 points. Lastly, the hybrid mode of monitoring (half remote/half in-person) was ranked with 77 points. Open-ended responses provided insights into the reasons behind these preferences, emphasising the importance of maintaining mobility, cognitive function and emotional well-being. The clinical team evaluated these findings, confirming that the selected attributes were both clinically relevant and aligned with patient priorities. This evaluation process ensured that the treatment specificities chosen for individualised care were comprehensive and reflective of patient needs.Conclusions By identifying and prioritising key treatment attributes, this research highlights the multifaceted nature of MS management and emphasises the importance of aligning treatment options with patient preferences. Addressing these factors through further quantitative preference assessments is essential for preventative MS care, improving patient outcomes and promoting a more patient-centred approach to treatment.